New material and phylogenetic position of the basal iguanodont dinosaur Delapparentia turolensis from the Barremian (Early Cretaceous) of Spain - Gasca, J.M.; Moreno-Azanza, M.; Ruiz-Omeñaca, J.I.; Canudo, J.I. (Journal of Iberian Geology, 2015)
Delapparentia turolensis Ruiz-Omeñaca, 2011 is the only iguanodont taxon erected in the Barremian of Spain. It is described on the basis of a partial postcranial skeleton discovered in the 1950s near the village of Galve (Teruel Province), within the Camarillas Formation. Recently, new remains from the same individual have been recovered, and these are described here. Furthermore, after first-hand examinations of the holotype, the phylogenetic position of this taxon has been analysed for the first time, and its diagnosis is emended. Delapparentia turolensis is a large-sized, basal iguanodont which presents an autapomorphic, unusually high axial neural spine and a unique combination of postcranial characters. The ilium morphology differs from that of other basal iguanodonts and relates Delapparentia to the Valanginian Barilium dawsoni from England, with whom it shares two synapomorphies. In our phylogenetic analysis Delapparentia is recovered in a polytomy with Kukufeldia, Lanzhousaurus, Barilium and the clade equivalent to Iguanodontoidea.